AKIBAT HUKUM PENERIMA DANA LAYANAN PENDANAAN BERSAMA BERBASIS TEKNOLOGI INFORMASI GAGAL BAYAR (Jurnal Magister Hukum Perspektif, 2023)
Technological innovations with financial features continue to emerge, marking the momentum of transformation in the financial world. Fintech Lending or Fintech Peer to peer Lending is a money lending and borrowing service in the financial sector with the use of information technology, this type provides loans for people's urgent needs. This technology-based financial service offers financial products that provide hope for people who need money. The effects that occur are problems for recipients of online loan funds because they are unable to pay so they are trapped in debt and the risk of defaulting on loans or known as "GalBay". The purpose of this research is to find out the binding that is born, the legal consequences and legal responsibilities of recipients of information technology-based joint funding service loans who default. The research method used is normative legal research, namely library law research including legal principles, and legal synchronization. The results of the research, regarding the binding on information technology-based joint funding services, namely the agreement made until the default committed by the recipient of the funds. The legal consequences of recipients of information technology-based joint funding services making default or default, are getting a warning from the Funder, will receive a penalty and interest expense according to the agreement on the electronic contract, Collection from other parties in collaboration with the Funder will be included in the SLIK blacklist of the Financial Services Authority. Meanwhile, the responsibility that can be imposed on the recipient of funds is that they are still obliged to pay off all loan installments along with penalty obligations in accordance with the agreed electronic agreement. The responsibility ends if the customer who defaults or fails to pay fulfills his obligations